Perovskite-type complex oxide and method for preparing the same
Patent Information
- Application Number
- KR1020240128311
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2044-09-23
Smart Images

Figure 112024103536312-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a perovskite-type composite oxide, and more specifically, to a perovskite-type composite oxide and a method for manufacturing the same. Background Technology
[0002] Hydrogen is recognized as a highly promising green energy source with significant potential for future clean energy applications and industrial production, and hydrogen production by water splitting in the industrial sector has increased significantly in recent years. Due to its eco-friendly characteristics, the demand for hydrogen continues to rise. Recently, various methods for hydrogen production are being researched.
[0003] For example, hydrogen is produced through methanol vapor reforming using a parabolic trough solar receiving reactor utilizing solar energy. However, the above method has the problem of incurring economic costs for reactor maintenance and management. Another example is producing hydrogen using a solar thermal thermochemical cycle. However, the solar thermal thermochemical cycle is a complex process and presents the difficulty of precisely controlling reaction elements such as temperature, pressure, and reactant flow rates.
[0004] Accordingly, photoconversion technology using semiconductor photocatalysts is gaining attention for its ability to efficiently utilize solar energy to convert it into chemical energy and for its environmental friendliness. Photocatalysts can accelerate the chemical reaction that separates water into hydrogen and oxygen using solar energy.
[0005] As a representative example of a photocatalyst, ABO3 structure perovskites are receiving attention for their excellent catalytic activity and structural characteristics. However, ABO3 structure perovskites have high band gap energies, which makes it difficult to apply them to actual products.
[0006] Therefore, it is necessary to develop photocatalysts with reduced band gap energy and improved structural, morphological, and optical properties. Prior art literature
[0007] Korean Registered Patent No. 10-256809 The problem to be solved
[0008] The objective of the present invention is to provide a perovskite-type composite oxide with improved crystallographic, structural, optical, and photocatalytic properties.
[0009] The object of the present invention is to provide a method for manufacturing a perovskite-type composite oxide with improved crystallographic, structural, optical, and photocatalytic properties. means of solving the problem
[0010] A perovskite-type composite oxide according to an exemplary embodiment can be represented by the following Formula 1.
[0011] [Equation 1]
[0012] AB 1 x B 2 (1-x) O3
[0013] A includes post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 comprises one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd, O is oxygen, and x is 0 <x<1이다.
[0014] In one embodiment, A may include Bi(bismuth).
[0015] In one embodiment, the B 1 It contains Ti (titanium), and the above B 2 It may include Mn(manganese).
[0016] In one embodiment, x may be 0.3≤x≤0.9.
[0017] In one embodiment, the perovskite-type composite oxide may include a nanostructure.
[0018] In one embodiment, the average diameter of the nanostructure may be 100 nm to 300 nm.
[0019] In one embodiment, the average crystal size of the nanostructure may be 80 nm to 130 nm.
[0020] In one embodiment, the nanostructure has an optical band gap energy (E) in the visible light wavelength region. g ) can satisfy the following range.
[0021] E g < 3.2(eV)
[0022] A method for preparing a perovskite-type composite oxide according to an exemplary embodiment may include the steps of: mixing a post-transition metal precursor, a first transition metal precursor, a second transition metal precursor, and a solvent to form a mixture; hydrothermally synthesizing the mixture to obtain a preliminary composite oxide; and annealing the preliminary composite oxide to obtain a composite oxide represented by Formula 1 below.
[0023] [Equation 1]
[0024] AB 1 x B 2 (1-x) O3
[0025] A includes post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 comprises one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd, O is oxygen, and x is 0 <x<1이다.
[0026] In one embodiment, x in Equation 1 may be 0.3≤x≤0.9.
[0027] In one embodiment, the post-transition metal precursor may include a bismuth salt, the first transition metal precursor may include a titanium alkoxide, and the second transition metal precursor may include a manganese salt.
[0028] In one embodiment, the hydrothermal synthesis may be carried out at 120 to 180°C for 1 to 10 hours.
[0029] In one embodiment, the annealing may be carried out at 300 to 600°C for 2 to 6 hours.
[0030] The photocatalyst according to an exemplary embodiment may include the perovskite-type composite oxide.
[0031] A solar cell according to an exemplary embodiment may include the perovskite-type composite oxide as a light-absorbing layer. Effects of the invention
[0032] The perovskite-type composite oxide according to the exemplary embodiment has excellent crystallographic, structural, optical, and photocatalytic properties.
[0033] For example, catalytic activity can be maintained for a long period due to minimal structural changes, and it exhibits excellent stability and durability.
[0034] For example, the band gap energy can be reduced to extend the light absorption range to visible light. Brief explanation of the drawing
[0035] Figure 1 is an FE-SEM image of the examples. FIGS. 2 (a) to (d) are SEM images of the surfaces of the examples. FIGS. 2 (e) to (h) are drawings showing the average diameters of the examples, and FIGS. 2 (i) to (l) are TEM images of the examples. Figure 3 is a FE-TEM image of the embodiments. Figure 4 (a) is an SEM image of Example 2, and Figures 4 (b) to (e) show the EDS (Energy Dispersive X-ray Spectroscopy) elemental mapping analysis of Example 2. Figure 5 is a diagram showing the XRD patterns of the embodiments. FIG. 6 (a) is a graph analyzing the UV-Vis spectrophotometers of the examples, and FIG. 6 (b) is a graph analyzing the band gap energies of the examples. Figure 7 is a diagram showing the photocurrent density measurement results of Example 1 and Example 4. FIG. 8 is a diagram briefly illustrating a method for manufacturing a perovskite-type composite oxide according to an exemplary embodiment. Specific details for implementing the invention
[0036] A perovskite-type composite oxide according to an exemplary embodiment of the present invention can be represented by Formula 1 below. The composite oxide has excellent crystallographic, structural, optical, and photocatalytic properties.
[0037] [Equation 1]
[0038] AB 1 x B 2 (1-x) O3
[0039] A includes post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 comprises one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd, O is oxygen, and x is 0 <x<1이다.
[0040] Hereinafter, the perovskite-type composite oxide of the present invention, the method for manufacturing the same, and the perovskite photocatalyst containing the same will be described in detail with reference to the examples and drawings. However, the present invention is not limited to these examples and drawings.
[0041] A perovskite-type composite oxide (hereinafter, composite oxide) according to an exemplary embodiment can be represented by the following Formula 1:
[0042] [Equation 1]
[0043] AB 1 x B 2 (1-x) O3
[0044] A includes post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 comprises one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd, O is oxygen, and x is 0 <x<1이다.
[0045] Generally, perovskite structures have a crystal structure of ABX3 (where A and B are cations and X is the anion binding them). Perovskites have a cubic structure where a B-site cation is located at the center and A-site cations can be located at each corner. The B-site cation can be surrounded by six anions to form a BO6 octahedron.
[0046] The composite oxide according to an exemplary embodiment may have a crystal structure of an A-site cation, a B-site cation, and an oxygen anion in a perovskite structure. For example, the B-site cation is B 2 The main cation is B 1 It may be partially substituted or doped with cations. For example, the composite oxide according to an exemplary embodiment may be used as a photocatalyst or in the light-absorbing layer of a solar cell.
[0047] For example, A could be a post-transition metal. Post-transition metals refer to metallic elements located in the p-block of the periodic table. They are situated between transition metals and metalloids, and their electronegativity is lower than that of transition metals but can be higher than that of alkali metals or alkaline earth metals.
[0048] For example, A may include one or more selected from Al, Ga, Ge, In, Sn, Sb, Tl, Pb, Bi, and Po. Preferably, A may include Bi (bismuth). When Bi is included, it can help to absorb wavelengths in the visible light region by adjusting the band gap energy, thereby increasing activity as a photocatalyst. It is chemically stable and has low toxicity, making it environmentally friendly.
[0049] For example, B 1 It may include one or more first transition elements selected from Zr, Y, Ti, V, and Cr. Preferably, B 1 It may contain Ti (titanium). When Ti is included, it can provide excellent photocatalytic properties and help control band gap energy by providing excellent optical properties in a specific wavelength range.
[0050] For example, B 2 It may include one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd. Preferably, B 2 It may contain Mn (manganese). Since Mn can have various oxidation forms, it is effective in controlling the light absorption characteristics of the material. It can help increase photocatalytic activity in the UV and visible light regions.
[0051] For example, in the above composite oxide, Bi cations may be located at the A-site and Mn cations at the B-site. For example, a portion of the B-site may be substituted or doped with Ti cations instead of Mn cations. Accordingly, crystallographic, structural, optical, and photocatalytic properties can be improved.
[0052] For example, the range of x is 0 <x<1일 수 있다. 예를 들어, x는 0<x<1을 만족하는 실수일 수 있다. 예를 들어, 식 1은 A가 Bi이고, B 1 is Ti, and B 2 If α is Mn, then Bi(Ti 0.1 Mn 0.9 )O3, Bi(Ti 0.2 Mn 0.8 )O3, Bi(Ti 0.3 Mn 0.7 )O3, Bi(Ti 0.4 Mn 0.6 )O3, Bi(Ti 0.5 Mn 0.5 )O3, Bi(Ti 0.6 Mn 0.4 )O3, Bi(Ti 0.7 Mn 0.3 )O3, Bi(Ti 0.8 Mn 0.2 )O3, Bi(Ti 0.9 Mn 0.1 It can be represented as )O3. Preferably, x can satisfy 0.3≤x≤0.9. Within the above range, the crystallographic, structural, optical, and photocatalytic properties of the composite oxide can be optimized.
[0053] In one embodiment, the composite oxide may be a nanostructure. The nanostructure is a nanomaterial, and its shape is not limited. For example, the nanostructure may be a nanorod, a nanoplate, a nanotube, a nanowire, a nanowire, a nanotetrapod, a nanooctapod, a nano dot-in-rod, a nanotripod, a nanobipod, or a nanoribbon.
[0054] In one embodiment, the average diameter of the nanostructure may be 100 to 300 nm. For example, the average diameter of the nanostructure is B located at the B-site. 1 and B 2 It can be adjusted according to the molar ratio or concentration. For example, B 1 As the molar ratio of increases, the average diameter of the nanostructure may decrease. For example, as the molar ratio of Ti increases, the average diameter of the nanostructure may decrease.
[0055] In one embodiment, the nanostructure may have a crystal lattice. The average crystal size of the nanostructure may be 80 to 130 nm. For example, the crystal size of the nanostructure is such that B is located at the B-site. 1 and B 2 It can be adjusted according to the molar ratio or concentration. For example, B 1 As the molar ratio of increases, the average crystal size of the nanostructure may decrease. For example, for example, B 1 As the molar ratio of increases, the lattice stripe spacing of the nanostructure may decrease. For example, as the molar ratio of Ti increases, the average crystal size or lattice stripe spacing of the nanostructure may decrease.
[0056] In one embodiment, the nanostructure has an optical band gap energy (E) in the visible light wavelength region. g ) can satisfy the following range.
[0057] E g < 3.2(eV)
[0058] For example, if the band gap energy of the above nanostructure is less than 3.2 (eV), it can absorb energy in the visible light wavelength range as well as UV, so the light absorption range can be expanded.
[0059] A method for preparing a perovskite-type composite oxide according to an exemplary embodiment may include the steps of: mixing a post-transition metal precursor, a first transition metal precursor, a second transition metal precursor, and a solvent to form a mixture; hydrothermally synthesizing the mixture to obtain a preliminary composite oxide; and annealing the preliminary composite oxide to obtain a composite oxide represented by Formula 1 below.
[0060] [Equation 1]
[0061] AB 1 x B 2 (1-x) O3
[0062] A includes post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 comprises one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd, and Cd, O is oxygen, and x is 0 <x<1이다.
[0063] Referring to FIG. 8, first, a mixture can be formed by mixing a post-transition metal precursor, a first transition metal precursor, a second transition metal precursor, and a solvent (e.g., S-10).
[0064] For example, the post-transition metal precursor may be a salt containing the post-transition metal. For example, it may be a salt containing any one of Al, Ga, Ge, In, Sn, Sb, Tl, Pb, Bi, and Po. Preferably, it may be a salt containing bismuth (Bi), for example, bismuth (III) nitrate pentahydrate (Bi(NO3)3·5H2O), but is not limited thereto.
[0065] For example, the first transition metal precursor may be a metal alkoxide. The metal may be, for example, Zr, Y, Ti, V, or Cr. Preferably, it may be a titanium alkoxide.
[0066] For example, the second transition metal precursor may be a salt containing any one of Mn, Fe, Co, Ni, Cu, Pd, and Cd. Preferably, it may be a salt containing Mn, for example, manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O), but is not limited thereto.
[0067] The prepared precursors can be mixed with a solvent to form a mixture. For example, any solvent capable of dissolving the precursors may be used. For example, it may include an aqueous hydrochloric acid solution, deionized water, etc. The solvent may further include organic solvents such as acetone and methyl alcohol.
[0068] When forming the above mixture, the molar ratio of the first transition metal precursor and the second transition metal precursor can be adjusted. For example, the molar ratio of the first transition metal precursor and the second transition metal precursor can be adjusted so that the molar ratio of the first transition metal at the B-site of the finally obtained composite oxide satisfies 0.3 to 0.9 and the molar ratio of the second transition metal satisfies 0.7 to 0.1.
[0069] Next, the above mixture can be introduced into a reactor to proceed with hydrothermal synthesis to obtain a preliminary composite oxide (e.g., S-20).
[0070] Hydrothermal synthesis refers to a method of synthesizing or growing crystals of, for example, metal salts, oxides, hydrates, or metal powders in a solution or suspension state by utilizing properties that depend on the solubility of the material, temperature, pressure, and solvent concentration.
[0071] The above reactor may use an autoclave capable of carrying out hydrothermal synthesis. A fluorine-doped tin oxide (FTO) glass substrate may be placed inside the autoclave. The FTO glass substrate can facilitate the hydrothermal synthesis step and provide a suitable environment necessary for the reaction, thereby promoting the growth of the finally obtained composite oxide.
[0072] In one embodiment, hydrothermal synthesis may be carried out at 120 to 180°C. Preferably, it may be carried out at 120 to 170°C, 130 to 170°C, or 130 to 160°C. In one embodiment, hydrothermal synthesis may be carried out for 1 to 10 hours. Preferably, it may be carried out for 1 to 8 hours, 2 to 8 hours, or 3 to 7 hours. When synthesis is carried out within the above temperature and time ranges, the finally obtained composite oxide may satisfy the aforementioned average diameter and average crystal size.
[0073] In some embodiments, the obtained pre-composite oxide can be washed. For example, residual ionic contaminants of the obtained pre-composite oxide can be removed by washing with ethanol or deionized water.
[0074] In some embodiments, the washed pre-composite oxide can be dried at 50 to 110°C for 1 to 60 minutes.
[0075] Next, the above-mentioned preliminary composite oxide can be annealed to obtain a composite oxide represented by the above-mentioned Formula 1 (e.g., S-30). The above-mentioned details can be applied to the specific description of the obtained composite oxide.
[0076] For example, annealing may be performed in air to improve structural properties. For example, annealing may be performed at 300 to 600°C. Preferably, it may be performed at 300 to 550°C or 350 to 500°C. For example, annealing may be performed for 2 to 6 hours, preferably 2 to 5 hours or 3 to 5 hours. Within the above range, the composite oxide finally obtained may satisfy the aforementioned average diameter and average crystal size. In addition, a composite oxide with excellent crystallographic, structural, optical, and photocatalytic properties may be provided.
[0077] A photocatalyst according to an exemplary embodiment may include the aforementioned perovskite-type composite oxide. The photocatalyst may have a band gap energy of less than 3.2 (eV). Therefore, it can react not only with UV light but also with light in the visible light region.
[0078] A solar cell according to an exemplary embodiment may include the aforementioned perovskite-type composite oxide as a light-absorbing layer.
[0079] In some embodiments, the solar cell may include a first electrode; an electron transport layer formed on the first electrode; a light absorption layer formed on the electron transport layer; a hole transport layer formed on the light absorption layer; and a second electrode formed on the hole transport layer.
[0080] For example, the first electrode may include at least one selected from indium tin oxide (ITO), fluorinated tin oxide (FTO), aluminum zinc oxide (AZO), boron-doped zinc oxide (BZO), niobium titanium oxide (NTO), zinc tin oxide (ZTO), and indium zinc tin oxide (IZTO).
[0081] For example, the electron transport layer is ZnO, ZnO:Al, ZnO:B, ZnO:Ga, ZnO:N, SnO, SnO2, ITO, TiO2, Cs2CO3, 6,6-phenyl-C 61 - Butylic acid methyl ester (PCBM(C61)), PCBM(C60), PCBM(C70), PCBM(C71), PCBM(C76), PCBM(C80), PCBM(C82), indene-C 60 bisadduct (ICBA) and 6,6-phenyl-C 61- Fullerene derivatives selected from butylic acid cholesteryl esters (PCBCR), polybenzimidazole, perylene, poly[[N,N'-bis(2-octyldodecyl)-napthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'-(2,2'-bithiophene)](NDI2OD-T2), naphthalene diimide(NDI)-selenophene copolymer(PNDIS-HD), poly[(E)-2,7-bis(2-decyltetradecyl)-4-methyl-9-(5-(2-(5-methylthiophen-2-yl)vinyl)thiophen-2-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H, It may include at least one selected from 7H)-tetraone] (PNDI-TVT), poly[[N,N′-bis(2-hexyldecyl)naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'-thiophene] (PNDI2HD-T), NiOx, and p-type oxide semiconductors.
[0082] For example, the light absorption layer may include a perovskite-type composite oxide prepared by the aforementioned perovskite-type composite oxide or a method for preparing a perovskite-type composite oxide.
[0083] For example, the hole transport layer comprises Spiro-OMeTAL, PTAA (poly(triarylamine), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), PEDOT:PSS (Poly(3,4-ethylenedioxythiophene doped with poly(styrenesulfonic acid), cyclopenta-[2,1-b;3,4-b']-dithiophene), benzothiadiazole, diketopyrrolopyrrole, thieno[3,4-b]thiophene, benzodithiophene, carbazole, fluorene, PEDOT:PSS (poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate), PS-PAA (polystyrenepolyacrylic acid block copolymer), poly-TPD (Poly(4-butylphenyl-diphenyl-amine)), PPV (polypheylen vinylene), PVP (polyvinylpyrrolidone), NiO x It may include at least one selected from a p-type oxide semiconductor.
[0084] For example, the second electrode may include at least one selected from silver (Ag), aluminum (Al), platinum (Pt), tungsten (W), copper (Cu), molybdenum (Mo), gold (Au), nickel (Ni), palladium (Pd), and carbon (C).
[0085] In some embodiments, the solar cell may have a structure in which a first electrode, an electron transport layer, a light absorption layer, a hole transport layer, and a second electrode are sequentially stacked.
[0087] Preferred embodiments and comparative examples of the present invention are described below. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.
[0089] Example 1: Bi(Ti 0.3 Mn 0.7 )O 3 Manufacturing of complex oxides (Nanorod)
[0090] A fluorine-doped tin oxide (FTO) glass substrate (TEC7, Sigma-Aldrich) with a surface resistance of approximately 7 Ω / sq was prepared by cutting it to a size of 2 cm × 2 cm using a diamond cutter. The prepared glass substrate was placed in an autoclave containing a Teflon liner with the conductive side facing downward.
[0091] 3.33 mL of bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar), titanium(IV) n-butoxide (C 16 H 36 1.00 mL of O4Ti (Alfa Aesar) and 2.33 mL of manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar) were added to a solvent containing 30 mL of 37% aqueous hydrochloric acid solution (Daejung Chemical) and 30 mL of deionized water (DI), and mixed for 30 minutes using a stirrer to prepare a homogeneous mixture.
[0092] The above mixture was added to an autoclave, and hydrothermal synthesis was carried out at 150°C for 6 hours. Subsequently, the autoclave was cooled to room temperature to obtain a preliminary composite oxide. The obtained preliminary composite oxide was washed with ethanol and deionized water, dried at 80°C for 30 minutes, and then annealed in air at 450°C for 4 hours to finally obtain the perovskite-type composite oxide Bi(Ti). 0.3 Mn 0.7 )O3 was manufactured.
[0093] Example 2: Bi(Ti 0.5 Mn 0.5 )O 3 Manufacturing of complex oxides
[0094] 2.00 mL of bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar), titanium(IV) n-butoxide (C 16 H 36 The procedure was carried out in the same manner as in Example 1, except that 1.00 mL of O4Ti (Alfa Aesar) and 1.00 mL of manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar) were used.
[0095] Example 3: Bi(Ti 0.7 Mn 0.3 )O 3 Manufacturing of complex oxides
[0096] 1.43 mL of bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar), titanium(IV) n-butoxide (C 16 H 36 The procedure was carried out in the same manner as in Example 1, except that 1.00 mL of O4Ti (Alfa Aesar) and 0.43 mL of manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar) were used.
[0097] Example 4: Bi(Ti 0.9 Mn 0.1 )O 3 Manufacturing of complex oxides
[0098] 1.11 mL of bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar), titanium(IV) n-butoxide (C 16 H 36 The procedure was carried out in the same manner as in Example 1, except that 1.00 mL of O4Ti (Alfa Aesar) and 0.11 mL of manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar) were used.
[0099] Comparative Example 1: SrTi 0.3 Mn 0.7 O 3 Manufacturing of complex oxides
[0100] The procedure was carried out in the same manner as in Example 1, except that strontium acetate tetrahydrate (Sr(C2H3O2)2·4H2O) was used instead of bismuth (III) nitrate pentahydrate.
[0101] Comparative Example 2: BiMnO 3 Manufacturing of complex oxides
[0102] Bismuth (III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar) and manganese (II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar) were each dissolved in distilled water to prepare 0.1 M aqueous solutions. The procedure was carried out in the same manner as in Example 1, except that the prepared aqueous solutions were mixed to prepare a mixture.
[0103] Comparative Example 3: BiTiO 3 Manufacturing of complex oxides
[0104] Bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar) and titanium(IV)n-butoxide (C 16 H 36 0.1M aqueous solutions were prepared by dissolving O4Ti and Alfa Aesar in distilled water, respectively. The procedure was carried out in the same manner as in Example 1, except that the prepared aqueous solutions were mixed to prepare a mixture.
[0105] Comparative Example 4: BiTi 0.1 Mn 0.9 O 3 Manufacturing of complex oxides
[0106] 10.00 mL of bismuth(III) nitrate pentahydrate (Bi(NO3)3·5H2O, Alfa Aesar), titanium(IV) n-butoxide (C 16 H 36 The procedure was carried out in the same manner as in Example 1, except that a mixture was prepared using 1.00 mL of O4Ti (Alfa Aesar) and 9.00 mL of manganese(II) acetate tetrahydrate (C4H6MnO4·4H2O, Alfa Aesar).
[0107] Comparative Example 5: Bi(Ti 0.3 Mn 0.7 )O 3 Manufacturing of complex oxides
[0108] The hydrothermal synthesis was carried out in the same manner as in Example 1, except that the hydrothermal synthesis temperature was 190°C instead of 150°C.
[0109] Comparative Example 6: Bi(Ti 0.3 Mn 0.7 )O 3 Manufacturing of complex oxides
[0110] The process was carried out in the same manner as Example 1, except that the annealing temperature was 700°C instead of 600°C.
[0112] Experimental Example 1: SEM / TEM Analysis
[0113] The surface morphology of the composite oxides according to the examples was measured using a field emission scanning electron microscope (FE-SEM; JSM-6500F, JEOL) and a field emission transmission electron microscope (FE-TEM; JEM-2100F HR, JEOL). FE-SEM analysis was performed at an acceleration voltage of 10 kV, and FE-TEM analysis was performed at an acceleration voltage of 200 kV. The results are shown in Figures 1 to 3.
[0114] Figure 1 is an FE-SEM image of a cross- section of a composite oxide according to the examples.
[0115] Referring to FIG. 1, the glass was coated with a SnO2 layer with a thickness of 0.605 μm, and it was confirmed that the composite oxide according to the example grew uniformly and vertically on the coating layer. In the examples, it was confirmed that the length of the composite oxide decreased significantly as the Ti molar ratio increased.
[0116] FIGS. 2 (a) to (d) are SEM images of the surface of the composite oxide according to the examples, FIGS. 2 (e) to (f) show the average diameter of the composite oxide according to the examples, and FIGS. 2 (i) to (l) are TEM images of the composite oxide according to the examples.
[0117] Referring to FIGS. 2 (a) to (d), it was confirmed that the composite oxide according to the example is evenly aligned and densely distributed, and has a uniform microstructure regardless of the ratio of Ti. Referring to FIGS. 2 (e) to (h), it can be seen that the average diameter of the composite oxide decreases as the Ti molar ratio increases. Referring to FIGS. 2 (i) to (l), it can be seen that the average diameter of the composite oxide decreases as the Ti molar ratio increases.
[0118] Figure 3 is a FE-TEM image of a cross- section of a composite oxide according to the examples.
[0119] Referring to FIG. 3, the lattice stripes of the composite oxide according to the examples can be observed, and it can be seen that they exhibit high crystallinity. It was confirmed that the spacing between the lattice stripes narrows as the Ti molar ratio increases, and it can be expected that Ti ions have been introduced into the lattice of the composite oxide.
[0120] Figure 4 (a) is an SEM image of a composite oxide according to Example 2, and Figures 4 (b) to (e) show the EDS (Energy Dispersive X-ray Spectroscopy) elemental mapping analysis of the composite oxide according to Example 2.
[0121] Referring to Figure 4, it can be seen that Ti, Bi, Mn, and O in the composite oxide are remarkably uniform.
[0123] Experimental Example 2: XRD Analysis
[0124] X-ray diffraction (XRD) patterns were analyzed using a Rigaku Ultima IV diffractometer with Cu Kα radiation (Kα = 1.541 A˚) at a continuous scan rate of 0.09˚ / min (2θ = 20~80˚). The surface composition of the sample was analyzed by X-ray photoelectron spectroscopy (XPS, Thermo VG K Alpha+).
[0125] Figure 5 is a diagram showing the XRD pattern of a composite oxide according to the examples.
[0126] Referring to Figure 5, the peaks at 36.26˚, 41.40˚, 62.99˚, 69.06˚, and 69.94˚ all confirmed that Ti ions are included in the complex oxide crystal lattice.
[0127] Additionally, the crystal size and strain of the composite oxides according to the examples and comparative examples were calculated by applying the Williamson-Hall and Uniform deformation models. The results are listed in Table 1.
[0128] Crystal size (nm) Strain (ε) Example 1 119.68 2.10×10 -3 Example 2 114.93 1.98×10 -3 Example 3 98.51 1.71×10 -3 Example 4 92.83 1.62×10 -3 Comparative Example 1 158.45 2.83×10 -3 Comparative Example 2 50.91 1.15×10 -3 Comparative Example 3 55.72 1.24×10 -3 Comparative Example 4 138.40 2.45×10 -3 Comparative Example 5 135.18 2.38×10 -3 Comparative Example 6 75.15 1.42×10 -3
[0129] Referring to Table 1, it can be seen that the crystal size of the composite oxide according to the examples is in the range of 80 to 130 nm. In addition, it can be confirmed that the crystal size of the composite oxide decreases as the Ti ion molar ratio increases. The decrease in the crystal size of the composite oxide with increasing Ti ion molar ratio may be attributed to the substitution of Ti ions with the B-site Mn of the composite oxide.
[0131] Experimental Example 3: UV-Vis Spectroscopic Analysis
[0132] The ultraviolet-visible (UV-Vis) spectrophotometers of the composite oxides according to the examples were analyzed (UV2600, Shimadzu), and the results are shown in Fig. 6 (a). The change in the band gap energy of the composite oxides was measured using the Tauc plot in Fig. 6 (b), and the results are listed in Table 2. The change in the band gap energy of the composite oxides according to the comparative examples was also measured and listed together in Table 2.
[0133] Optical band gap energy (eV) Example 1 3.158 Example 2 3.146 Example 3 3.141 Example 4 3.132 Comparative Example 1 3.507 Comparative Example 2 2.928 Comparative Example 3 2.037 Comparative Example 4 3.216 Comparative Example 5 3.289 Comparative Example 6 3.274
[0134] Referring to FIG. 6 (a), the composite oxide according to the examples is Ti A red shift can be observed as the ion molar ratio increases. It can be seen that the absorption wavelength of the composite oxide in the example is extended into the visible light range due to Ti ion substitution.
[0135] Referring to Figure 6 (b) and Table 2, it can be seen that the optical band gap energy of the composite oxide according to the examples decreases as the Ti molar ratio increases.
[0137] Experimental Example 4: Photocurrent Density Analysis
[0138] An electrode was prepared using a composite oxide according to the example as the working electrode, Ag / AgCl as the reference electrode, Pt as the auxiliary electrode, and KOH as the electrolyte. The current density was measured by irradiating visible light and UV using the electrode and a potentiostat. The results are shown in Fig. 7.
[0139] In Fig. 7, "Light on" means that UV irradiation has started, and the range from -0.8V to 0.7V is the region where only visible light is irradiated.
[0140] Referring to Fig. 7, it can be seen that the current density increases around 0.5V when only visible light is irradiated (purple box). It can be seen that the current density of the composite oxide according to the example increases more as the Ti molar ratio increases (Example 4). Therefore, it can be confirmed that the light absorption range of the composite oxide according to the example extends to the visible light region.
[0141] In addition, the photocurrent density at a voltage of 1.5V was measured at the electrode containing the composite oxide according to the example and comparative example and is listed in Table 3.
[0142] Photocurrent density (mA / cm²) 2 ) Example 1 3.19±0.19 Example 2 3.25±0.11 Example 3 4.64±0.17 Example 4 5.54±0.25 Comparative Example 1 3.01±0.01 Comparative Example 2 2.97±0.13 Comparative Example 3 2.98±0.27 Comparative Example 4 3.02±0.08 Comparative Example 5 2.89±0.08 Comparative Example 6 2.99±0.24
[0143] Referring to Table 3, the examples show that the photocurrent density value of the electrode is approximately 3.19 mA / cm². 2 While the above-mentioned high values were shown, the comparative examples showed lower photocurrent density values compared to the examples.
Claims
Claim 1 Perovskite-type complex oxide represented by the following Formula 1: [Formula 1]AB 1 x B 2 (1-x) O3A contains post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 contains one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd and Cd, O is oxygen, and x is 0.3≤x≤0.
9. Claim 2 In claim 1, the above A is a perovskite-type complex oxide comprising Bi(bismuth). Claim 3 In paragraph 1, the above B 1 It contains Ti (titanium), and the above B 2 is a perovskite-type complex oxide containing Mn(manganese). Claim 4 delete Claim 5 In claim 1, the perovskite-type composite oxide comprises a nanostructure. Claim 6 In claim 5, the perovskite-type composite oxide having an average diameter of the nanostructure of 100 nm to 300 nm. Claim 7 In claim 5, a perovskite-type composite oxide having an average crystal size of the nanostructure of 80 nm to 130 nm. Claim 8 In claim 5, the nanostructure has an optical band gap energy (E) in the visible light wavelength region. g Perovskite-type complex oxide satisfying the following range: E g < 3.2(eV) Claim 9 A method for preparing a perovskite-type composite oxide of claim 1, comprising the steps of: mixing a post-transition metal precursor, a first transition metal precursor, a second transition metal precursor, and a solvent to form a mixture; hydrothermally synthesizing the mixture to obtain a preliminary composite oxide; and annealing the preliminary composite oxide to obtain a composite oxide represented by the following Formula 1: [Formula 1]AB 1 x B 2 (1-x) O3A contains post-transition metals, and B 1 ... comprises one or more first transition elements selected from Zr, Y, Ti, V, and Cr, and B 2 contains one or more second transition elements selected from Mn, Fe, Co, Ni, Cu, Pd and Cd, O is oxygen, and x is 0.3≤x≤0.
9. Claim 10 delete Claim 11 A method for manufacturing a perovskite-type composite oxide according to claim 9, wherein the post-transition metal precursor comprises a bismuth salt, the first transition metal precursor comprises a titanium alkoxide, and the second transition metal precursor comprises a manganese salt. Claim 12 A method for preparing a perovskite-type composite oxide according to claim 9, wherein the hydrothermal synthesis is carried out at 120 to 180°C for 1 to 10 hours. Claim 13 A method for preparing a perovskite-type composite oxide according to claim 9, wherein the annealing is carried out at 300 to 600°C for 2 to 6 hours. Claim 14 A photocatalyst comprising a perovskite-type composite oxide according to any one of claims 1 to 3 and claims 5 to 8. Claim 15 A solar cell comprising a perovskite-type composite oxide according to any one of claims 1 to 3 and claims 5 to 8 as a light-absorbing layer.
